Innovative Flipped Classroom Learning in Improving Critical Thinking Skills in Elementary School Students - Viera Setyani; Widia Ningsih; Nur Afni Pratiwi; Sugianoor; Siti Munfiatik (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
This study aims to explore the application of the innovative Flipped Classroom learning model to improve critical thinking skills in elementary school students. The Flipped Classroom model reverses the traditional learning sequence by providing learning materials to students before face-to-face sessions, allowing class time to be used for discussion, collaboration, and problem-solving. Through this approach, students are encouraged to be more active, independent, and reflective in the learning process. The research method used was a descriptive qualitative study using observation, interviews, and documentation techniques with teachers and fifth-grade students at an elementary school in Indonesia. The results indicate that the implementation of the Flipped Classroom significantly improves indicators of critical thinking skills, such as the ability to analyze, evaluate, and summarize information. These findings contribute to the development of learning strategies that align with the demands of the Independent Curriculum, which emphasizes differentiated learning and the strengthening of critical thinking skills.